MC68000 microprocessor development board - Cheong, Kee Loan (2007)
The 68000 microprocessor becoming an increasingly important microprocessor in today's market, as evidenced by the frequent announcements of products using the 68000. The chip is expandable by design, and Motorola has produce a full 32-bit version in 1984. The 68000 is considerably more complex than many of the 16-bit minicomputers popular since the 1970s. The main purpose of the MC68000 microprocessor development board is to educate the coming generation of engineers and programmers about the 68000, with the expectation that they will able to learn, understand, and design their own systems that will be using the 68000 microprocessor. In addition to its intended audience of educators and students, this board is of interest to both high school student and the others which involved in learning and developing of the 68000-based system. This system will consist of two board which is the main board and the application board. The application board consist of various types of input and output devices such as 4x4 keypad, DIP switch, traffic light LED, DC motor, 7 segment display, dot matrix, and LCD. This prototype of 68000 microprocessor based development board will be able to produce various types of outputs according to the input given where it is able to be manipulated by programming the memory unit.